J. G. BALLARD’S INNER SPACE: THE JUXTAPOSITION OF TIME, SPACE AND BODY - Groppo, Pedro (Em Tese, 2009)
The fiction of J. G. Ballard is unusually concerned with spaces, both internal and external. Influenced by Surrealism and Freudian psychoanalysis, Ballard’s texts explore the thin divide between mind and body. This analysis of the story “The terminal beach” illustrates well some of the concepts present throughout his fiction.